2019
DOI: 10.1016/j.cub.2019.11.031
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for an S cone contribution to acute neuroendocrine and alerting responses to light

Abstract: SummaryExposure to even moderately bright short-wavelength light in the evening can strongly suppress the production of melatonin and delay our circadian rhythm. These effects are mediated by the retinohypothalamic pathway, connecting a subset of retinal ganglion cells to the circadian pacemaker in the suprachiasmatic nucleus (SCN) in the brain. These retinal ganglion cells express the photosensitive protein melanopsin, rendering them intrinsically photosensitive (ipRGCs). But ipRGCs also receive input from th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 10 publications
4
42
3
Order By: Relevance
“…Intracellular recording from the macaque retina has shown that melanopsin pRGCs are inhibited by the short-wavelength cones (S cones), whilst the rods and medium-wavelength cones provide an excitatory input [ 60 ]. By contrast, recent studies in humans have failed to find evidence for an S cone contribution to acute neuroendocrine and alerting responses to light [ 138 ]. Finally, multiple lines of evidence from behavioral studies have implicated an input from the rods and cones [ 40 , 139 , 140 , 141 ], not least the finding that Opn 4 -/- (knockout) mice still show circadian entrainment, albeit in an attenuated form [ 67 , 68 , 69 ].…”
Section: The Discovery and Characterization Of The 3rd Retinal Phomentioning
confidence: 99%
“…Intracellular recording from the macaque retina has shown that melanopsin pRGCs are inhibited by the short-wavelength cones (S cones), whilst the rods and medium-wavelength cones provide an excitatory input [ 60 ]. By contrast, recent studies in humans have failed to find evidence for an S cone contribution to acute neuroendocrine and alerting responses to light [ 138 ]. Finally, multiple lines of evidence from behavioral studies have implicated an input from the rods and cones [ 40 , 139 , 140 , 141 ], not least the finding that Opn 4 -/- (knockout) mice still show circadian entrainment, albeit in an attenuated form [ 67 , 68 , 69 ].…”
Section: The Discovery and Characterization Of The 3rd Retinal Phomentioning
confidence: 99%
“…In total, the evidence from such studies [29][30][31][32][33][34][35][36][37] supports the view that, under most practically relevant situations (extended exposures to polychromatic light in the absence of pharmacological pupil dilation), light-sensitivity of human physiological responses can be reliably approximated by the α-opic irradiance for melanopsin or the corresponding EDI (melanopic EDI). Moreover, based on the consistency of melanopic irradiance-response relationships across studies 32 , it is now possible to define realistic, evidence-based recommendations for light exposures that target non-visual responses.…”
Section: The Need For Guidancementioning
confidence: 80%
“…While data from two such studies are compatible with the possibilities that S-cones 38 or the photopic system 24 may contribute alongside melanopsin, a large body of data with and without use of pupil dilation indicates that for exposures of an hour or more, melatonin suppression can be reliably predicted by melanopic EDI 31,32,39,40 . This conclusion is further strengthened by findings from recent studies that have employed photoreceptor isolating stimuli to confirm that melanopsin-selective modulations in irradiance modulate melatonin production 34,35 but failed to find any effect of large variations in irradiance selectively targeting S-cones 36 . Further evidence consistent with a dominant role for melanopsin comes from earlier observations showing that totally visually blind humans (where remaining light responses match the spectral sensitivity expected for melanopsin) 18,20 can display near-full melatonin suppression 10,12,18 , as do individuals with colour-vision deficiencies 41 .…”
Section: Evidence From Laboratory Studiesmentioning
confidence: 82%
See 2 more Smart Citations